Genomic biosurveillance detects a sexual hybrid in the sudden oak death pathogen - Richard C. Hamelin; Guillaume J. Bilodeau; Renate Heinzelmann; Kelly Hrywkiw; Arnaud Capron; Erika Dort; Angela L. Dale; Emilie Giroux; Stacey Kus; Nick C. Carleson; Niklaus J. Grünwald; Nicolas Feau (Communications Biology, 2022)
Genome sequencing of isolates of the pathogen responsible for sudden oak death in the United States and sudden larch death in Europe reveal hybridisation between European and American lineages.